Inflammatory markers activation associated with vapor or smoke exposure in Wistar rats - Wawryk-Gawda, Ewelina; Zarobkiewicz, Michał K.; Wolanin-Stachyra, Marta; Opoka-Winiarska, Violetta (Frontiers in Immunology, 2025)
Electronic cigarettes (e-cigarettes) were introduced two decades ago as a safer alternative to traditional cigarettes, aiming to assist in smoking cessation. However, the global use of e-cigarettes has surged, with the highest prevalence among adolescents and young adults. Despite their popularity, the safety of e-cigarettes remains controversial, with emerging evidence linking their use to various health risks, including cardiovascular issues, respiratory diseases, and a condition known as e-cigarette or vaping use-associated lung injury (EVALI). In this study, we investigated the inflammatory response in rats exposed to e-cigarette vapor compared to traditional cigarette smoke. We measured the serum concentrations of inflammatory markers such as IL-10, IFN-γ, IL-5, IL-2, TNF-α, GM-CS, IL-4, IL-9, IL-17F, IL-17A, IL-13, and IL-22 in the serum of rats subjected to 6 weeks of exposure. We assessed the activation of Nf-κb, Stat3, and Socs3 genes and the expression of CXCL2 in lung tissues. Our results revealed a significant increase in proinflammatory cytokines, particularly in the vapor-exposed group. We did not observe any statistically significant difference in the activation levels of Nf-κb, Stat3, and Socs3 between the groups of rats, but we noted the predictable correlations between IL-22 and IL-2, IL-6 and IL-2, IL-9 and IL-2, IL-6 and IL-9, IL-22 and IL-17F, IL-6 and IL-17F, IL-6 and IL-5, IL-2 and IL-17F, IL-13 and IL-4, and IL-5 and IL-4. In IHC staining, we observed a higher number of CLCX2-positive cells in the lung tissues in groups 2 and 3 compared to the control group. Interestingly, after a 2-week cessation period, inflammatory markers largely normalized, except for IL-17F and IL-13, which remained elevated in the cigarette smoke-exposed group. Our results suggest that while e-cigarette use may trigger a potent inflammatory response, the effects may be reversible upon cessation, albeit with some cytokines persisting longer in traditional cigarette users. Although the immune response has normalized, the increased tendency toward lung fibrosis may lead to permanent structural changes. Further research is needed to fully elucidate the clinical implications of these findings and assist in implementing legal regulations regarding the availability of e-cigarettes in the market.